Patent Foramen Ovale and Thromboembolic Complications - Fazio, Giovanni; Ferro, Giovanni; Barbaro, Giuseppe; Fattouch, Kalil; Ferrara, Filippo; Novo, Giuseppina; Novo, Salvatore (Current Pharmaceutical Design, 2010)
The foramen ovale, an atrial septal defect, which is essential in the fetal circulation, remains patent through adulthood in approximately 25% of the general population and therefore it represents the most common persistent abnormality of fetal origin. Patent foramen ovale (PFO) allows interatrial right-to-left blood shunting during those periods of the cardiac cycle in which the right atrial pressure exceeds the left one. An increasing number of pathological manifestations of PFO has been recently identified; among these, paradoxical systemic embolism, refractory hypoxemia in patients with right ventricular myocardium infarction or severe pulmonary disease, orthostatic oxygen desaturation in the rare platypnea-orthodeoxia syndrome, neurological decompression illness in divers, high altitude pilots and astronauts, and finally, migraine headache with aura. Nowadays, many techniques allow to detect a PFO. In this study, we investigated each of them, assessing their potential diagnostic role even in comparison with the main features of the other methods.
Keywords: cryp-togenetic ictus